The Analysis of Shifts in Form and Meaning in Subtitle Drama 等到烟暖雨收 (Děngdào Yān Nuǎn Yǔ Shōu) from Mandarin to Indonesian - Vivi Adryani Nasution; Nia Angelina Pakpahan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explain the shifts in form and shifts in meaning that occur in Subtitle Drama 等到烟暖雨收 (děngdào yān nuǎn yǔ shōu) from Mandarin to Indonesian. This study uses the classification of shifts in form based on Catford's theory, shifts in meaning based on the theories of Vinay and Dabelnet. The research method used is descriptive qualitative and uses the observation method and note-taking techniques for data collection. Based on the results of the analysis, there are 116 data shifts in form and 11 data shifts in meaning. 60.9% of shifts in form fall into the category of shifts in structure, and 54.5% of shifts in meaning fall into the category of abstract to concrete. Occurs because words cannot be directly translated from Mandarin into Indonesian due to cultural differences.